Digital processing for non-stationary narrow-band interference suppression in fading channels - Kasparis, Takis; Nelson, Russell S. (My University, 1994)
The suppression of narrow-band interference has long been a concern in Direct-Sequence Spread Spectrum (DS-SS) Communication Systems. Recently, transform domain processing (TDP) approaches have been used to suppress intentional interference. This paper extends previous work done in the area of TDP utilizing non-linear rank order filters, namely conditional median filters (CMFs). The paper confronts problems incurred in Rayleigh distributed fading channels. A solution is suggested by introducing a normalized adaptive median filter. This adaptive approach considers each received bit independently and uses a normalization metric to compensate for fading. The paper also presents bit error rates (BER) for a DS-SS receiver employing the proposed approach. Using Monte-Carlo simulations the BER of the fading channel was determined for various jammer and fading scenarios, and results are presented.
Keywords: Electric filters; Digital signal processing; Adaptive filters; Digital filters; Radio--Interference